Curcumin induces apoptosis and protective autophagy in castration-resistant prostate cancer cells through iron chelation - Yang C; Ma X; Wang Z; Zeng X; Hu Z; Ye Z; Shen G (Dove Medical Press, 2017)
Chunguang Yang,1,* Xueyou Ma,1,* Zhihua Wang,1 Xing Zeng,1 Zhiquan Hu,1 Zhangqun Ye,1 Guanxin Shen2 1Department of Urology, Tongji Hospital, 2Department of Immunology, Tongji Medical College, Huazhong University of Science and Technology, Wuhan, Hubei, People’s Republic of China *These authors contributed equally to this work Background: Curcumin induces apoptosis and autophagy in different cancer cells. Moreover, chemical and biological experiments have evidenced that curcumin is a biologically active iron chelator and induces cytotoxicity through iron chelation. We thus hypothesized that curcumin may induce apoptosis and autophagy in castration-resistant prostate cancer (CRPC) cells through its iron-chelating properties.Materials and methods: CRPC cells were loaded with curcumin alone or in combination with ferric ammonium citrate (FAC). Cytotoxicity was measured by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay. Apoptosis was assessed by flow cytometry, terminal deoxynucleotidyl transferase nick end labeling (TUNEL) assay and caspase activity. Autophagy status was analyzed by the detection of autophagosomes and light chain 3-II (LC3-II) using transmission electron microscopy and Western blot. Iron-binding activity of curcumin was assessed by spectrophotometry and MTT assay. The expression levels of transferrin receptor 1 (TfR1) and iron regulatory protein 1 (IRP1) were examined by Western blot.Results: Curcumin induced apoptosis and autophagy in CRPC cells. Combining curcumin with autophagy inhibitors (3-methyladenine [3-MA]) synergized the apoptotic effect of curcumin. Moreover, curcumin bound to FAC at a ratio of ~1:1, as assessed by spectrophotometry and MTT assay. Apoptosis and autophagy induced by curcumin were counteracted by equal amounts of FAC. At apoptosis- and autophagy-inducing concentrations, curcumin enhanced the expression levels of TfR1 and IRP1, indicative of iron deprivation induced by curcumin.Conclusion: Together, our results indicate that curcumin induces apoptosis and protective autophagy in CRPC cells, which are at least partially dependent on its iron-chelating properties. Keywords: curcumin, castration-resistant prostate cancer, apoptosis, autophagy, iron chelation